2018
DOI: 10.3390/children5020016
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Apps for Calming, Relaxation, and Mindfulness Interventions for Pediatric Palliative Care Patients

Abstract: Patients and families increasingly use mobile apps as a relaxation and distraction intervention for children with complex, chronic medical conditions in the waiting room setting or during inpatient hospitalizations; and yet, there is limited data on app quality assessment or review of these apps for level of engagement, functionality, aesthetics, or applicability for palliative pediatric patients. The pediatric palliative care study team searched smartphone application platforms for apps relevant to calming, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 8 publications
1
22
0
3
Order By: Relevance
“…37 However, more studies are needed to explain the fearrelief mechanism of those applications. 38 The anxiety levels of parents might also affect their children's anxiety. Kain et al 39 found that parents play a major role in pediatric patient preoperative preparation and that family-centered care improves perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, more studies are needed to explain the fearrelief mechanism of those applications. 38 The anxiety levels of parents might also affect their children's anxiety. Kain et al 39 found that parents play a major role in pediatric patient preoperative preparation and that family-centered care improves perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Others have used the online platform to deliver talking therapies, which usually take place face to face, such as cognitive behavioural therapy (CBT; Karyotaki et al, 2018;Kallestad et al, 2018). Others provide information such as psychoeducation and methods of engagement with self-help (Weekly, Walker, Beck, Akers & Weaver, 2018). Overall, as a method of mental health care deliverance, e-health has proven efficacious (Bakker, Kazantzis, Rickwood & Rickard, 2016;Rathbone & Prescott, 2017) and can be a valid source of reassurance (Prescott & Mackie, 2017).…”
Section: Online Help Seekingmentioning
confidence: 99%
“…Advanced pain management for children with serious illness often requires multimodal analgesia. This describes an approach of utilizing multiple analgesic agents (such as basic analgesia, opioids, adjuvant analgesia), regional anesthesia (such as nerve blocks or neuroaxial analgesia), rehabilitation (such as physical therapy, motor graded imagery), psychological (such as cognitive behavioral therapy) and integrative (formally known as “non-pharmacological”) therapies (such as massage, hypnosis) which usually act synergistically for more effective pediatric pain control with fewer side effects than a single analgesic or modality [ 34 , 35 , 36 , 37 ].…”
Section: Common Myths and Misconceptions In Pediatric Palliative Cmentioning
confidence: 99%